New Book. Marianna Castiglione and Ida Oggiano, Giving Voice to Silence: Material and Immaterial Evidence of the Female World and Childhood from the Coroplastic Perspective. Proceedings of the Webinar (September 21–22, 2022), (Transformations and Crisis in the Mediterranean, 1), Roma: CNR Edizioni, 2024, DOI:https://doi.org/10.19282/tcm.01.2024 - Marianna Castiglione; Ida Oggiano (Les Carnets de l’ACoSt)
The open access volume examines terracotta figurines depicting women and children discovered in Cyprus, the Levant, the Greek world, Sardinia, and the Iberian Peninsula, and dating from the Bronze Age to the Hellenistic period. It explores their iconography, typology, archaeological contexts, and potential meanings to reassess the roles of these two social groups in ancient Mediterranean societies. This research contributes to a broader understanding of the material and immaterial dimensions of women’s and children’s lives, challenging their traditional marginalization in historical narratives.